Vegetative Growth of Green Eggplant Due to Treatment of Vermicompost and NPK Fertilizer - Ahmad Raksun; Moh. Liwa Ilhamdi; I Wayan Merta; I Gde Mertha (Jurnal Biologi Tropis, 2021)
Green eggplant is native to the tropics. Green eggplant is one of the most popular vegetable ingredients in Indonesia. The availability of nutrients in the growing media is one of the most determining factors for the growth and yield of green eggplant. Research on vegetative growth of green eggplant due to vermicompost and NPK fertilizer treatment has been carried out from April to August 2021. This study aims to determine: (1) vegetative growth of green eggplant due to vermicompost treatment, (2) green eggplant vegetative growth due to NPK fertilizer treatment, (3) green eggplant vegetative growth due to interaction of vermicompost and NPK fertilizer treatment. This research was conducted in a factorial completely randomized design with three replications. The first factor is the application of NPK fertilizer which consists of 4 levels and the second factor is the treatment of vermicompost which consists of 5 levels. Research data were analyzed using analysis of variance. The results showed: (1) treatment of NPK fertilizer with different doses significantly effected the number of leaves, stem diameter, leaf length, and stem height of green eggplant. The optimum dose of NPK fertilizer was 2 grams for one plant, which produced the number of leaves, diameter stems, leaf length and stem height of green eggplant were better than treatments at other doses. (2) The treatment of vermicompost had a significant effect on the number of leaves, stem diameter, leaf blade length, and stem height of green eggplant, the optimum dose of vermicompost was 1.8 kgÃÂ  for 1 m2 of agricultural land, resulting in stem diameter, number of leaves, leaf length and green eggplant stem height was better than other treatments (3) the interaction of vermicompost and NPK fertilizer had no significant effect on stem diameter, number of leaves, leaf length and stem height of green eggplant.